Study of sexual behaviours with different types of estrus synchronization protocols in Boer goats - Mohamad Salleh, Suraya; Hassan Basri, Abdul Mu'in; Yaakub, Halimatun (Colegio Brasileiro de Reproducao Animal, 2021)
There is still a lack of information on estrus synchronization in goats. Understanding the estrus synchronization protocols and the subsequent effects is important to improve the efficiency of assisted reproductive technologies (ARTs) and subsequently would improve the breeding procedures. This study will help in determining the most suitable estrus synchronization protocol and understand better the effect on the sexual behaviour and hormonal effects in goats. A total of 127 Boer does were used and divided into three groups with different duration of CIDR insertion intravaginally either for 14 (two groups) or 9 days (one group). Approximately 0.5 ml Estrumate® (PG) was administered intramuscularly to all groups at CIDR removal, and only groups PMSG14 and PMSG9 were administered with 200IU of Pregnant Mare Serum Gonadotropin (PMSG) intramuscularly. Estrus signs were observed at 4 h intervals and blood samples were collected for progesterone and luteinizing hormone determination. The percentage of does in estrus within 24 to 72 h post CIDR removal was significantly higher (P<0.05) in groups with PMSG compared to the group without the PMSG. The numbers of does display estrus signs within 24 to 28 h post CIDR removal were significantly higher (P<0.05) in group shorter period (9 days) compared to groups with 14 days CIDR. The P4 concentrations at 24 hours post CIDR removals and LH concentration was not significantly different (P>0.05) in all groups. The time of the LH peak in the group without the PMSG was significantly delayed (P<0.05) when compared to group 9 days CIDR and administered with PMSG. It is recommended to use the treatment for 9 days CIDR since the estrous cycle can be shortened.